2020
DOI: 10.1177/2324709620966862
|View full text |Cite
|
Sign up to set email alerts
|

Isoproterenol Causing Coronary Vasospasm and ST Elevations During Tilt Table Testing

Abstract: Syncope is a sudden but reversible brief loss of consciousness secondary to an acute reduction of cerebral perfusion. Reflex syncope denotes neurologically mediated syncope, which includes vasovagal, carotid sinus syndrome, and other situational syncope. The most frequent form of syncope is vasovagal, which is triggered by emotional stress or prolonged standing, and may be diagnosed with the tilt table test. A thorough investigation of syncope is necessary as serious cardiovascular disorders may also be a caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…Traditionally, most ST-segment deviations seen on remote cardiac monitoring is reported as ST-segment depressions, indicating episodes of transient ischemia. 27 - 30 These early studies hinted at the value of identifying transient ST-segment changes as valuable, particularly, as it identified patients at higher risk. 29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, most ST-segment deviations seen on remote cardiac monitoring is reported as ST-segment depressions, indicating episodes of transient ischemia. 27 - 30 These early studies hinted at the value of identifying transient ST-segment changes as valuable, particularly, as it identified patients at higher risk. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, most ST-segment deviations seen on remote cardiac monitoring is reported as ST-segment depressions, indicating episodes of transient ischemia. [27][28][29][30] These early studies hinted at the value of identifying transient ST-segment changes as valuable, particularly, as it identified patients at higher risk. 29 Aside from improvement in the quality of tracings, MCOT devices also offer the availability of continuous listening; recording every heartbeat for up to 30 days with the flexibility of storing data locally or when needed, data can be transmitted in real time for immediate assessment as seen in our case.…”
Section: Discussionmentioning
confidence: 99%
“…However, none of the patients in this very small study reported any chest pain or shortness of breath, and the ECG changes all resolved shortly after cessation of isoprenaline. Kumar et al 9 and Duong et al 10 both reported cases of chest pain and inferior ST-elevation after isoprenaline administration. In both cases, the patient’s symptoms and ECG improved after sublingual nitroglycerine administration, and subsequent coronary angiography showed no obstructive coronary artery disease, raising the likelihood that these presentations were due to coronary spasm.…”
Section: Discussionmentioning
confidence: 99%
“…Angina refers to cardiac pain or discomfort triggered by strenuous activities. Several experimental angina models, such as vasopressin-, methacholine- and isoproterenol-induced angina models, have been used for studying angina [ 16 , 17 , 18 ]. Further, several indirect indicators such as ST-segment, blood pressure, and biochemical markers of myocardial injury are used to evaluate angina [ 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although several mechanisms, such as inflammation, apoptosis, microvascular dysfunction, and oxidative stress, are involved in I/R injury [ 15 ], the relationship of angina and I/R injury is still insufficiently understood. Even though vasopressin, methacholine, and isoproterenol, which evoke vasospasm, have been used as experimental animal models for angina [ 16 , 17 , 18 ], they have less translational potential.…”
Section: Introductionmentioning
confidence: 99%